2017
DOI: 10.1038/s41598-017-08903-0
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stabilized Core-Satellite Gold Nanoassemblies in Vivo: DNA-Directed Self-Assembly, PEG Modification and Cell Imaging

Abstract: Au nanoparticles (NPs) have important applications in bioimaging, clinical diagnosis and even therapy due to its water-solubility, easy modification and drug-loaded capability, however, easy aggregation of Au NPs in normal saline and serum greatly limits its applications. In this work, highly stabilized core-satellite Au nanoassemblies (CSAuNAs) were constructed by a hierarchical DNA-directed self-assembly strategy, in which satellite Au NPs number could be effectively tuned through varying the ratios of core-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Among various noble metal nanomaterials, gold nanomaterials are most intensely investigated as imaging contrast agents and nanocarriers . As a result, the integration of aptamer with gold nanomaterials, such as Au nanorods (AuNRs), Au nanoparticles, Au nanocages, Au nanostars (AuNSs), hollow gold nanospheres (HAuNS), and Au nanoclusters (Au NCs), has been widely employed in in vivo applications in diverse areas, such as intracellular molecular imaging, cancer cell and tumor imaging, targeted delivery of therapeutic cargos (e.g., anticancer drug, protein, and gene), and cancer therapy . In one example, Huang et al demonstrated the use of AuNRs as an efficient and robust multivalent platform for molecular assembly of aptamers for targeted cell imaging .…”
Section: Molecular Engineering Of Aptamer‐based Nanomaterials Toward mentioning
confidence: 99%
See 1 more Smart Citation
“…Among various noble metal nanomaterials, gold nanomaterials are most intensely investigated as imaging contrast agents and nanocarriers . As a result, the integration of aptamer with gold nanomaterials, such as Au nanorods (AuNRs), Au nanoparticles, Au nanocages, Au nanostars (AuNSs), hollow gold nanospheres (HAuNS), and Au nanoclusters (Au NCs), has been widely employed in in vivo applications in diverse areas, such as intracellular molecular imaging, cancer cell and tumor imaging, targeted delivery of therapeutic cargos (e.g., anticancer drug, protein, and gene), and cancer therapy . In one example, Huang et al demonstrated the use of AuNRs as an efficient and robust multivalent platform for molecular assembly of aptamers for targeted cell imaging .…”
Section: Molecular Engineering Of Aptamer‐based Nanomaterials Toward mentioning
confidence: 99%
“…These nanoconjugates showed promising application for T1 MRI of transplanted human brain neural stem cells in vivo. Afterward, Tang et al constructed highly stabilized core satellite Au nanoassemblies (CSAuNAs) by a hierarchical DNA‐directed self‐assembly strategy, which can be selectively accumulated in the kidneys with satisfactory renal retention capability. Similarly, Si et al developed versatile drug‐loaded nanoprobes based on MUC1 aptamer‐integrated AuNPs, and further engineered telomerase‐recognition sequence to the nanoprobes, enabling controllable drug release by intracellular telomerase …”
Section: Molecular Engineering Of Aptamer‐based Nanomaterials Toward mentioning
confidence: 99%
“…While smaller inorganic nanoparticles such as gold, silver, or semiconductor NPs as satellites are explored. The nano spacer linkers that are commonly employed include (1) protein based assembly 41 , (2) polymeric based assembly [42][43][44] , (3) DNA -assisted assembly 36, [45][46][47][48][49] , and (4) molecular linkers that directly bridge the plasmonic units using either covalent or electrostatic interactions of the functional groups 37,50-52 . For example, Chen et al demonstrated the synthesis of streptavidin-coated polymeric bead core -Au satellite assembly via DNA linkers 53 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of DNA is often laborious and expensive. Typically, DNA mediated core-satellite assemblies require at least ~17 hours to finish the reaction with many subsequent centrifugation steps 36, [45][46][47][48][49] . Moderate enhancing capabilities are observed within the DNA mediated assembly due to the intrinsic DNA length required to ensure stable hybridization precluding tunability of the interparticle gap distances between the core-satellite nanostructures 53,54 .…”
Section: Introductionmentioning
confidence: 99%
“…DNA-Au nanoparticle (DNA-AuNP) conjugates, one of the most versatile hybrid bionanomaterials, provide excellent platforms for chemical and biological applications, such as biosensing, cellular imaging, drug delivery, and therapeutics. In general, the nanoconjugates typically turn to physical or chemical interaction to self-assemble oligonucleotides on the AuNPs surfaces. For the first type, DNA is adsorbed onto the surfaces of AuNPs with a random coil structure via noncovalent interaction. , The preparation process of such DNA-AuNPs is simple and time-saving; however, their applicability is greatly confined since the physically based nanoconjugates merely tolerate the concentration of 20 mM NaCl in the solution according to the previous report, and thereby they are incapable of stably existing in the complicated biological matrix.…”
mentioning
confidence: 99%